2015
DOI: 10.3389/fncel.2015.00020
|View full text |Cite
|
Sign up to set email alerts
|

Interference of TRPV1 function altered the susceptibility of PTZ-induced seizures

Abstract: Transient receptor potential vanilloid 1 (TRPV1) is widely distributed in the central nervous system (CNS) including hippocampus, and regulates the balance of excitation and inhibition in CNS, which imply its important role in epilepsy. We used both pharmacological manipulations and transgenic mice to disturb the function of TRPV1 and then studied the effects of these alterations on the susceptibility of pentylenetetrazol (PTZ)-induced seizures. Our results showed that systemic administration of TRPV1 agonist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 45 publications
(61 reference statements)
1
25
0
3
Order By: Relevance
“…Furthermore, the severity of PTZ‐induced tonic‐clonic seizures was decreased in TRPV1‐deficient mice . Surprisingly, decreased severity of PTZ‐induced tonic‐clonic seizures was also reported in mice with an overexpression of TRPV1 channels in the hippocampus . The severity of PTZ‐induced seizures was also reduced after intrahippocampal administration of either TRPV1 channel agonist or antagonist .…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Furthermore, the severity of PTZ‐induced tonic‐clonic seizures was decreased in TRPV1‐deficient mice . Surprisingly, decreased severity of PTZ‐induced tonic‐clonic seizures was also reported in mice with an overexpression of TRPV1 channels in the hippocampus . The severity of PTZ‐induced seizures was also reduced after intrahippocampal administration of either TRPV1 channel agonist or antagonist .…”
Section: Discussionmentioning
confidence: 89%
“…11 Surprisingly, decreased severity of PTZ-induced tonic-clonic seizures was also reported in mice with an overexpression of TRPV1 channels in the hippocampus. 22 The severity of PTZ-induced seizures was also reduced after intrahippocampal administration of either TRPV1 channel agonist or antagonist. 22 Thus, it has been suggested that in mice with TRPV1 channel overexpression, PTZ administration was not able to further increase TRPV1 channel function and neuronal excitability in the hippocampus, leading to decreased seizure susceptibility 22 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Another group of potential molecular targets of CBD, TRP channels, such as TRPV 1 have also been proposed as potential mediators of the antiepileptic effects of CBD (De Petrocellis and . Although the precise role of TRPV 1 in the regulation of network excitability has not yet been fully elucidated, and may depend on the experimental paradigm (Manna and Umathe 2012;Jia et al 2015;von Rüden et al 2015a), it has been suggested that TRPV 1 is phosphorylated by increased neuronal activity and that the main function of CBD (and also cannabidivarin) is to trigger TRPV 1 dephosphorylation, thereby desensitizing the ion channel and thus reducing excitability to produce an antiepileptic effect (Iannotti et al 2014). Finally, perhaps one of the most exciting recent development is the potential antagonistic effect of CBD on the recently characterized G-protein-coupled receptor GPR55 (Ryberg et al 2007).…”
Section: Potential Neurobiological Mechanisms Of the Antiepileptic Efmentioning
confidence: 99%